Empowering Paud Teachers Through Montage Activities to Enhance Children’s Motor and Language Skills - Asmara, Berda; Rahayu, Dewi Widiana; Aquariza, Novi Rahmania (Indonesia Berdaya, 2025)
This community engagement program was designed to enhance the pedagogical skills of early childhood educators by introducing montage-based learning as an innovative method to support children's fine motor and language development. The program was implemented at a rural early childhood education center in Pasuruan, Indonesia, where a significant number of children exhibited limited motor and verbal abilities, and teachers had not previously applied montage as a structured learning and evaluation tool. The program involved a series of activities, including needs assessment, training workshops, guided classroom implementation, and evaluation using a custom-designed assessment rubric. The results showed significant improvements in both teacher competence and student engagement. Teachers demonstrated increased confidence and creativity in planning and conducting montage activities, while children displayed better coordination and expressive language skills during and after the intervention. The developed rubric was found to be effective in capturing children's developmental progress in a structured manner. Overall, the program successfully empowered educators to integrate art-based methods into their teaching strategies, resulting in a more engaging and developmentally supportive learning environment. This approach holds promise for broader application in other early childhood education contexts to address similar pedagogical challenges.